2019
DOI: 10.1029/2019jd031381
|View full text |Cite
|
Sign up to set email alerts
|

Flood Inundation Generation Mechanisms and Their Changes in 1953–2004 in Global Major River Basins

Abstract: Despite the serious threats posed by floods, the driving mechanisms of floods are still not well understood. Here we apply a physically based inundation model coupled with a river routing model (Model for Scale Adaptive River Transport (MOSART)) within the Energy Exascale Earth System Model (E3SM) framework to investigate flood inundation dynamics. After calibration using observed streamflow and satellite-derived flood extent, the model is used to simulate global flood inundation from 1953 to 2004. The mean da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 89 publications
(147 reference statements)
0
30
0
Order By: Relevance
“…Zhou et al (2020) developed two‐way coupling between ELM and MOSART with water management to constrain the irrigation amount by water available in the streams and reservoirs. Mao et al (2019) evaluated a MOSART floodplain inundation parameterization (Luo et al, 2017) globally and studied flood generation mechanisms and their historical changes. The stream temperature, water management, and floodplain inundation modules, as well as the two‐way coupling of ELM and MOSART with irrigation and water management, are being integrated into E3SM v2 for enhanced capabilities to represent human‐Earth system interactions.…”
Section: Highlights Of Modeling Challenges and Simulation Resultsmentioning
confidence: 99%
“…Zhou et al (2020) developed two‐way coupling between ELM and MOSART with water management to constrain the irrigation amount by water available in the streams and reservoirs. Mao et al (2019) evaluated a MOSART floodplain inundation parameterization (Luo et al, 2017) globally and studied flood generation mechanisms and their historical changes. The stream temperature, water management, and floodplain inundation modules, as well as the two‐way coupling of ELM and MOSART with irrigation and water management, are being integrated into E3SM v2 for enhanced capabilities to represent human‐Earth system interactions.…”
Section: Highlights Of Modeling Challenges and Simulation Resultsmentioning
confidence: 99%
“…Sutanudjaja et al (), for instance, used global datasets of both environmental and human variables to setup a global hydrological‐water resources model. Mao et al () utilized datasets of observed streamflow and satellite‐derived inundation extents to simulate 50 years of flood extents in major river basins across the globe. de Graaf, Gleeson, van Beek, Sutanudjaja, and Bierkens () used data on climate and human water demand to setup and run a global surface water‐groundwater model, exploring the influence of groundwater pumping on environmental water flows.…”
Section: Dataset Applicationsmentioning
confidence: 99%
“…Sutanudjaja et al (2018), for instance, used global datasets of both environmental and human variables to setup a global hydrological-water resources model. Mao et al (2019) demand to setup and run a global surface water-groundwater model, exploring the influence of groundwater pumping on environmental water flows. Lack of data on human behavior has been compensated in model parametrization by employing environmental data.…”
Section: Human Influence On Hydrologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, the proportion of flood disasters in global natural disasters has been rising [1]. A flood disaster is a comprehensive response of many driving processes, including meteorological forcing, basin morphology (altitude, slope), geological characteristics, and human activities [2][3][4].…”
Section: Introductionmentioning
confidence: 99%